MICROCONTROLLER BASED HYDROGEN SULFIDE (H2S) MONITORING IN BIOGAS SYSTEM - Diah Yuniarti; Sarjiya -; Ambar Pertiwiningrum (Master in Systems Engineering, 2013)
Energy issue, particularly related to fossil fuel, is one the main issues today. Biogas is a new and renewable energy issued in National Research Agenda (ARN) 2010-2014 to overcome the energy crisis problem. A so called purification process is used to remove contaminants in biogas, including H2S in order to improve the standard requirement of biogas application. In this research, H2S concentration in biogas system is measured and monitored by H2S monitoring system.The hardware system comprises of piping and microcontroller AVR 8535 systems while the software system comprises of codes written in Delphi 7.0 and Code Vision AVR Eval. The result of the system is displayed on LCD or computer to enable the monitoring process by operator. The monitoring of H2S sensor responses will be carried out for recycled BFA size of 60+100 mesh and -200 mesh.Experiment has been conducted for sensor warming up time and response time for H2S and CH4 sensor, calibration process for H2S sensor and filter column. Based on sensor calibration experiment, transfer function of TGS825 sensor from calibration is y = 0.0203x + 27.153. The best adsorption model which represents BFA adsorption of biogas from tofu waste in the research is Thomas model.